2015
DOI: 10.1039/c5sc00476d
|View full text |Cite
|
Sign up to set email alerts
|

Electrode initiated proton-coupled electron transfer to promote degradation of a nickel(ii) coordination complex

Abstract: Electrochemical analysis of a nickel compound that degrades permitted a peek into the decomposition mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 63 publications
8
74
0
Order By: Relevance
“…Significant attention has been drawn to whether electrocatalysis in organic solvents is of homogeneous or heterogeneous nature. More specifically, several studies on similar dithiolene‐ or thiolate‐containing systems have shown that under reductive conditions a molecular catalyst may decompose to form a material which deposits on the surface of the electrode and is responsible for the catalytic performance . Several diagnostic criteria have been used to identify if a process is truly catalytic, most notably rinse tests in which the electrode, after a scan or a potential has been applied for a period of time, is transferred to a fresh solution containing only the acid.…”
Section: Discussionmentioning
confidence: 99%
“…Significant attention has been drawn to whether electrocatalysis in organic solvents is of homogeneous or heterogeneous nature. More specifically, several studies on similar dithiolene‐ or thiolate‐containing systems have shown that under reductive conditions a molecular catalyst may decompose to form a material which deposits on the surface of the electrode and is responsible for the catalytic performance . Several diagnostic criteria have been used to identify if a process is truly catalytic, most notably rinse tests in which the electrode, after a scan or a potential has been applied for a period of time, is transferred to a fresh solution containing only the acid.…”
Section: Discussionmentioning
confidence: 99%
“…and Dempsey et al . have attributed similar observations to the vulnerability of Ni−S bonds, which leads to electrochemical degradation of the catalyst in acidic media . Under these conditions, the homogeneous catalyst may become a precursor for a heterogeneous catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[10] In recent years, researchers have begun to investigate these transformations, however, only a few examples have been reported. [10][11][12][13][14][15][16][17][18][19][20][21] These studies have included both molecular Ni and Co complexes that undergo degradation and have highlighted the susceptibility of complexes that contain C=N bonds, N-O bonds, and/or Ni-S bonds. While a number of examples of Fe-based H 2 -evolving catalysts have been reported, [22][23][24] including many Fe-hydrogenase mimics, [4,[25][26][27][28] occurs through hydrogenation of the Schiff-base ligands, [18] we targeted the Fe analogue.…”
Section: Introductionmentioning
confidence: 99%